Education of Saiyid Said, son of H.H. the Sultan of Muscat - East India Company; Āl Bū Sa‘īd, Sa‘īd bin Taymūr; Āl Bū Sa‘īd, Sayyid Taymūr bin Fayṣal bin Turkī (British Library, 1926)
Correspondence on the education of Saiyd Sa'id bin Taimur [Sa‘īd ibn Taymūr], son of the Sultan of Muscat, Taimur bin Faisal. Letters discuss his education at Mayo College, Ajmer in a school for the sons of Indian rulers. The Sultan, Taimur bin Faisal [Taymūr ibn Fayṣal] wished him to attend a school suitable for Arabs, partly to improve his Arabic. The American Missionary School in Beirut was considered by British officials but the Sultan felt this was not suitable. Letters discuss a school in Baghdad and necessary arrangements such as the rent of a house.
Keywords: Vie politique -- Oman -- 1913-1932

Report on Sur. By Major G. P. Murphy, I.A., Indian Political Department, Political Agent, Muscat - Murphy, Gerald Patrick (British Library, 1929)
Report on Sur by Major Gerald Patrick Murphy, Political Agent of Muscat, dated 9 October 1928. It is divided into the following sections: I. – 'Geographical Description of Sur' – including an introduction to the tribes who inhabit it; II. – 'Historical Summary of the Bani Bu Ali' – including their origin, religion, engagements, expeditions, and feuds; III. – 'Historical Summary of the Jenebeh' – including their origin, feuds, criminal activities, and fines; IV. – 'The Slave Trade at Sur' – including British efforts in the suppression of the slave trade, treaties, a description of a captured slave vessel, and use the of the French flag as protection for slaving operations; V. – 'Summary of recent Events in Sur' – including the building of new forts, establishment of a new customs post, the question of the Sultan's authority, criminal activities, and customs dues; VI. – 'Review of the Situation at Sur' – including the policy pursued so far, request for assistance by the Sultan, the value of Sur in terms of prestige, and the form of assistance to be taken; appendix 1. – 'Early History of Sur'; appendix 2. – 'Wrecks and Piracy'.
Keywords: Vie politique -- Oman -- 1913-1932

Muscat: 1908-1928 - East India Company (India Office, 1928)
Document outlining the administration and history of Muscat from 1908-28. Covering: administration – Sultan of Oman succession history; treaty relations; internal administration by Council of Ministers; role of the Political Agent, Muscat; and the responsibility for expenditure; 1908 to 4 October 1913: Sultan Faisal – the successful suppression of arms traffic from Muscat; internal history of Muscat from the accession of Sultan Taimur, 4 October 1913 to 1928 – conditions for recognition of Sayid Taimur as ruler by His Majesty's Government; inefficiency of internal administration; proposals by the Political Agent for active interference in internal affairs by the Government of India and His Majesty's Government; the programme of reform accepted by the Sultan as condition of a loan; the results of the reform and loan; negotiations with Omani tribes; financial situation and the decision to employ a British Financial Advisor; relations between the Sultan of Muscat and Oman and the Ibadhi Tribes of Oman – the Oman Rebellion, 1913-21; foreign relations of Muscat, 1908-28 – treaty relations with France; relations with the United States of America, Dutch Government, Germany, Persia, and Ibn Saud [‘Abd al-‘Azīz bin ‘Abd al-Raḥmān bin Fayṣal Āl Sa‘ūd]; miscellaneous questions – the Muscat Order in Council; proposal for the establishment of a British Naval Base in the Musandim [Musandam] Peninsula; cession of Gwadur; oil in Muscat. It also includes a summary, lists points referred to in connection with the Persian Gulf Sub-Committee, and states the view expressed by the Government of India. Written by John Gilbert Laithwaite of the India Office.
Keywords: Vie politique -- Oman -- 1913-1932

Memorandum. (a) the Sultanate of Muscat and Oman. (b) His Highness the Sultan Saiyid Taimur Bin Faisal bin Turki - East India Company (British Library, 1928)
Typescript memorandum (marked 'Book Copy' in the top left corner of the first page) giving information about the Sultanate of Muscat and Oman under the following headings: Territory, Historical, Physical Features, Climate, Population, Products and Trade, Religion, and Government (folios 150-154); and about Sultan Saiyid Taimur Bin Faisal bin Turki [Taymūr bin Fayṣal], including comments on his appearance, habits, religious practices, political principles, sons, health, pastimes, and wealth (folios 154-155).
Keywords: Vie politique -- Oman -- 1913-1932

Soldiers of the Prophet - Murphy, C. C. R (J. Hogg, 1921)
Keywords: Vie politique -- Oman -- 1913-1932